Vector Computers in a World of Commodity Clusters, Massively Parallel Systems and Many-Core Many-Threaded CPUs: Recent Experience Based on an Advanced Lattice Boltzmann Flow Solver - Zeiser, Thomas; Hager, Georg; Wellein, Gerhard (High Performance Computing in Science and Engineering '08: Transactions of the High Performance Computing Center, Stuttgart (HLRS) 2008, 2009)
This report summarizes experience gained during the last year using the NEC SX-8 at HLRS and its wide range of competitors: commodity clusters with Infiniband interconnect, massively parallel systems (Cray XT4, IBM BlueGene L/P) and emerging many-core many-threaded CPUs (SUN Niagara2 processor). The observations are based on low-level benchmarks and the use of an advanced lattice Boltzmann flow solver developed in the framework of an international development consortium (ILBDC).
UnivIS-Import:2015-04-20:Pub.2009.tech.IMMD.phleir._vecto